Estudos do papel do gene Rad51 de tripanossomatídeos na recombinação e no reparo de DNA - Danielle Gomes Passos Silva (2010)
Trypanosoma cruzi is the etiologic agent of Chagas disease. This parasite can resist high doses of gamma radiation, a DNA double-strand breakinducing agent. To better understand this process, our group characterized the T. cruzi gene encoding one of the key proteins involved in homologous recombination, and double strand break repair, TcRad51. After gamma radiation treatment, epimastigote forms increase TcRad51 protein levels, followed by foci formation of TcRad51 in the nucleus. On the other hand, TcRad51 single allele knockout cells showed a delay in the induction of TcRad51 protein levels and in the formation of TcRad51 foci that were less intense than in wild type parasites. T. cruzi cells overexpressing TcRad51 display more intense foci prior to gamma radiation. The localization and the levels of TcRad51 contribute to distinct phenotypes of recovery after gamma radiation treatment. Parasites overexpressing TcRad51 present a growth recovery earlier than wild type cells whereas the TcRad51 single allele knockout cells present a delay in growth recovery following irradiation. Overexpression of TcRad51 also confers an increased resistance to zeocin, another agent that cause double strand DNA breaks, when compared to wild type parasites. In addition, using pulse field gel electroforesis (PFGE), we observed a difference in the levels of fragmentation of genomic DNA after exposition to gamma radiation, with the kinetics of chromosomal reconstitution being faster in TcRad51 overexpressing cells than in wild type cells. Aiming to evaluate the contribution of TcRad51 for the resistance to high doses of gamma radiation presented by T. cruzi, the effect of TcRad51 expression was evaluated in bloodstream forms of T. brucei parasites, which are much more sensitive to gamma radiation. Rad51 knockouts of T. brucei were generated and transfected with TcRad51 or TbRad51. The parasites expressing TcRad51 showed higher resistance to agents that cause double strand breaks in DNA than the parasites re-expressing TbRad51. However, the parasites expressing TcRad51 and TbRad51 have the same recombination capacity as measured by integration of DNA fragments in the genome. The roles of Rad51 in the repair of DNA crosslink and DNA oxidative lesions were also evaluated in this study. T. cruzi parasites overexpressing TcRad51 and TcRad51 heterozygous mutants have the same sensitivity to agents that induce DNA crosslink as UV light and cisplatin as wild type cells. Rad51 knockouts in T. brucei do not show differences in sensitivity to cisplatin compared to wild type parasites. Furthermore, overexpression of Rad51 in T. cruzi confers greater resistance to treatment with hydrogen peroxide and benzonidazole while TcRad51 heterozygous mutants are more sensitive than wild type cells. Similarly, Rad51 knockouts in T. brucei are more sensitive than wild type cells when treated with hydrogen peroxide. Therefore, Rad51 does not have a predominant role in the repair of DNA crosslink but, is a key protein for the repair of double strand breaks and DNA oxidative lesions both in T. cruzi and T. brucei